MOTIVASI PEMUDA PADA PROGRAM YESS (YOUTH ENTREPRENEUR AND EMPLOYMENT SUPPORT SERVICES) DI KECAMATAN TOMBOLO PAO, KABUPATEN GOWA: MOTIVASI PEMUDA PADA PROGRAM YESS (YOUTH ENTREPRENEUR AND EMPLOYMENT SUPPORT SERVICES) - Akbar Akbar; Nailah Husain; Ahmad Riyadi (Universitas Wahid Hasyim, 2026)
This study looks at why young people in Tombolo Pao District, Gowa Regency, are motivated to take part in the YESS (Youth Entrepreneur and Employment Support Services) program. A total of 80 respondents participated in the sample procedure, which was conducted using a random sampling approach. Quantitative descriptive analysis is the data analysis method employed. The study's findings indicate that self-actualization, social motivation, and economic incentive are the three primary factors that affect teenage engagement. Self-actualization achieved a high level with a score of 3.86, social motivation was at a moderate level, and economic motivation received a high score of 3.58 among these three variables. These findings show that youth are mainly motivated by the desire to improve their economic conditions and develop their potential, although social involvement still needs to be strengthened.